Russia's Oil Dependence and the EU - Torbjörn Becker (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2016)
Russia's macro economic fate has for a long time been connected to its vast natural resources and oil in particular. This paper shows just how deep Russia's dependence on oil is when it comes to its macro economic development (at least) since the break up of the Soviet Union. Although many analysts and policy makers discuss Russia's oil dependence, not everyone fully appreciates its quantitative importance and what it means for Russian policy making. This paper provides a detailed analysis of the link between Russia's economic growth and international oil prices, both when it comes to actual outcomes and the forecasts that are crucial for policy makers and other economic actors. The strength of the relationship is staggering. Depending on measures and time periods used, international oil prices account for 50 to over 90 percent of Russia's actual growth or forecast errors. Since international oil prices are exogenous to Russian policy makers it means that they do not really control the fate of their economy. Good macro economic management, in particular a flexible exchange rate, can mitigate some macro economic volatility that are due to changes in international oil prices but structural reforms to support diversification are needed to take control of the country's macro economic future. Investors and consumers in the EU could be Russia's prime partners to make this happen and it would benefit a vast majority of citizens both in Russia and the EU. However, it will require significant policy changes on both sides that currently look doubtful for other reasons than simple economics.
Keywords: E01; E02; E60; F00; 330; Russia; Macro; Oil; European Union